EP-369 Examining EphA2 expression in Colorectal Cancer. (9th August 2022) - Lyons, Nicholas; Hooper, John; Kryza, Thomas; Clark, David; Riddell, Andrew
Abstract: Aims: EphA2 is a potential therapeutic target for the treatment of colorectal cancer (CRC), however reports of EphA2 expression in CRC are inconsistent and often lack the context of a normal tissue comparator. The aim of this investigation is to undertake a detailed assessment of EphA2 protein expression across a range of pathological and normal specimens. Methods: 177 patient specimens (100 paired primary and normal colon, 42 paired primary and metastasis and 35 unpaired samples as part of a multi-tumour TMA) underwent immunohistochemical analysis (IHC) probing for EphA2 expression alongside a normal tissue array. Results: Weak/moderate EphA2 expression was noted in normal tissues of the proximal GI tract (stomach, small intestine) with little expression in the colon/rectum with a significant upregulation of EphA2 noted in primary lesions compared to matched normal tissue controls (p<0.0001). No difference in expression between stage of disease, sex or effect of patient age, location of samples (edge vs centre), stage of disease, T-stage or N-stage. EphA2 expression was significantly higher in primary lesions associated with M1 disease primaries (p=0.03). No difference in EphA2 expression was noted between matched primary and metastatic lesions (p>0.05). Conclusion: In this study, EphA2 protein expression was significantly higher in CRC lesions compared to healthy tissue (p<0.0001) with no diminution noted across a wide range of stages or lesion types. On this basis, diagnostic or therapeutic interventions targeting EphA2 are likely to be useful across a wide spectrum of disease.